An Analysis of Load Balancing Algorithm Using Software- Defined Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A data center is one of the secured space which serves as a house for many disks, switches, servers, routers, and several other hardware for a computer. It is a hardware solution for users who are present near the data center. Cloud Computing (CC) is the newer version of the data center which is capable of giving computer services to the users. Cloud service is the one which provides the users with data center set up when needed or preferred by the user themselves. In general cloud network service will be limited to a particular location or zone. In case if the target area of the user is near then the server will complete the action needed for the user. Only certain servers can provide service for the user in such cases some servers will remain idle. If the provided service by the servers is not used properly this may also lead to the issue of processing and managing a larger set of traffic which is one of the difficult tasks to perform. More network traffic may lead to giving more amount of pressure and complexity to the data center. In such a case Load Balancing (LB) is the preferred process for reducing the network failure and degradation process of the entire network. Software-defined networking is one the upcoming process which is capable of managing the entire network and also gives a general view about the network and its further configuration which needed to be upgraded. In this research paper, a software-defined network is developed for LB algorithms. In this paper, a Dynamic Server LB algorithm (Dserv- LB) is used for open-flow switches in the software-defined network system. This algorithm is one of the packet type LB algorithm. The request in the server is directly forwarded to the web-server with a higher level of server resources. From the result of the proposed algorithm, it was found that Dserv-LB is capable of improving the performance of the entire network and properly uses the server resource.